Characteristics of liquid smoke nanoencapsulation with a combination of maltodextrin and gum arabic as co-encapsulant - Angga Pramana; Kurnia Utami; Purnama Darmadji; Pudji Hastuti; Bara Yudhistira (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
The development of powder-type liquid smoke synthesis by the nanoencapsulation method was proposed to overcome the difficulties in handling liquid smoke. In the liquid form, liquid smoke was unpractical and difficult to distribute and transportation. Otherwise, phenolic compounds were easy to deteriorate (oxidize) during storage. The aims of this research to determine the character of nanocapsules by the spray drying process, involving water content, water activity (Aw), color, solubility, total phenolic compounds, functional group (FTIR), phenolic compounds staining, nanocapsules morphology profiles, and also efficiency phenolic compounds in the spray drying process. Resulted nanocapsule has a color intensity 85.17 ± 1.13; a -0.45 ± 0.11 and 9.2 ± 0.13 b; water content 5.92 ± 0.12%, water activity 0.26 ± 0.01 and 85.02 ± 0.33% solubility. Scanning Electron Microscope (SEM) results showed nanocapsule form was round and wrinkled. This optimization process obtained particles with nanometer dimensions and in recovery efficiency of phenolic compounds in the spray drying process of 47.36%. These results have the potential to be applied to the development of the food industry.